THE IMPACT OF STORAGE TEMPERATURE ON MORPHO-PHYSIOLOGICAL CHANGES AND SHELF LIFE OF MANGO CV. SINDRI - KIRAN, S; KHAN, AH; IQBAL, M; HUSSAIN, R; IQBAL, J; IQBAL, A; KHADIJA, F; BASHIR, MA (Biological and Clinical Sciences Research Journal, 2024)
The preservation of mango quality during storage is crucial for extending shelf life, reducing post-harvest losses, and ensuring consumer satisfaction. This study examined the impact of different storage temperatures on the quality attributes of mangoes (cv. Sindri) over a storage duration of 0, 7, 14, 21, and 28 days. Mangoes were stored at 8°C, 12°C, and 16°C. The study evaluated pH, titratable acidity, total soluble solids, vitamin C content, total phenolic content, total flavonoid content, color changes, and sensory qualities. Results indicated that the pH increased with higher storage temperatures, while titratable acidity and total soluble solids decreased, with the least reduction observed at 8°C. Vitamin C, phenolic, and flavonoid contents also declined, with minimal reductions at 8°C. Color changes were minor at 8°C but significant at 16°C. Sensory evaluation showed the best texture, flavor, aroma, appearance, and overall acceptability at 8°C. The impact of storage duration was significant, with most parameters showing a consistent decline in quality over time, particularly after 21 and 28 days. Thus, storing mangoes at 8°C effectively preserves their quality attributes during storage